Factors Affecting Contraceptive Use Among Married Women of Reproductive Age in Dolpo-Buddha Rural Municipality, Nepal - Lama, Tsering Youdon (Journal of Multidisciplinary Research Advancements, 2025)
In Nepal, a significant gap exists between knowledge and use of family planning, particularly in remote areas. This study assessed the factors affecting contraceptive use among married women of reproductive age (MWRA) in the remote, high-altitude Dolpo-Buddha Rural Municipality, Dolpa. A community-based cross-sectional study was performed involving 255 MWRA, chosen through population proportion sampling. Data were gathered via in-person interviews employing a semi-structured questionnaire. Chi-square tests and descriptive statistics were used to analyse the data. The mean age of respondents was 31.96 (±6.68) years. Most were illiterate (81.6%) and farmers (57.3%). While 75.7% knew about contraception, only 14.1% had adequate knowledge. The contraceptive prevalence rate among those with knowledge was high (89.3%), with implants (Norplant) being the most used method (66.3%). Irregular menstruation was the main cause of dissatisfaction (94.7%) and the most common side effect (81.6%). The majority of users (57.4%) did not obtain counselling. There were strong links between contraceptive use and the woman’s education (p=0.002), job (p=0.031), number of living children (p=0.01), talking to a partner (p=0.036), and making decisions together (p=0.024). Although many people used it, there was a significant lack of comprehensive knowledge and counselling. Stigma is a big problem. Interventions must focus on enhancing knowledge, ensuring counselling accessibility, and addressing socio-cultural barriers through targeted advocacy and partner engagement.